The concept of a joint criminal enterprise and domestic modes of liability for parties to a crime: a comparison of German and English law - Hamdorf, Kai (Journal of international criminal justice, 2007)
The concept of a Joint Criminal Enterprise (JCE) has become a useful tool in international criminal law. It allows courts to hold individuals criminally liable for group activities to which they have contributed in a criminally relevant way. The concept allows for an attribution of criminal responsibility of unforeseen consequences of such group activities, and it seems to enable the prosecution and the courts to extend criminal liability to high-level perpetrators that use subordinated persons for their criminal aims. The advantages of such a tool are obvious since the crimes under international criminal law are mostly of a systematic, large-scale and collective character, while domestic criminal law mainly deals with less complex crimes that are normally committed by individuals who can easily be linked to the crime. Due to this empirical or criminological fact, it seems logical that the normal modes of liability for parties to a crime used in domestic criminal law need to be adapted, and that a rather extensive assignment of criminal liability for secondary parties is justified in international criminal law. This article seeks to question this assumption by undertaking a comparative analysis of domestic modes of liability. The author aims to show, on the one hand, to what extent the concept of JCE is in line with the general concept of parties to a crime in domestic criminal law. On the other hand, the author argues that abandoning the idea of JCE as an independent mode of liability may lead to better compliance with the principles of legality and individual criminal responsibility and thereby increase the legitimacy of international criminal law